Estabelecimento de protocolo para criopreservação de sementes de Araucaria angustifolia (Bertol) O. Kuntze - Scolari, Tiago (2017)
Araucaria angustifolia (Bertol.) O. Kuntze is one of the native species from southern Brazil with economic and ecological importance. In recent decades, due to deforestation for timber marketing and expansion of agriculture, this species joined the list of those threatened with extinction. One of the ways to preserve A. angustifolia is per seed conservation, as it is the main process for the species propagation. However, the seeds of A. angustifolia endue recalcitrant behavior, not tolerating desiccation and low temperatures for long time. For this reason, it is necessary to look at alternatives for the conservation of the A. angustifolia seeds. One of the techniques that might be useful is cryopreservation, which consists in storing the propagules in liquid nitrogen at -196°C. However, several conditions must be met to achieve success, such as reducing the moisture of the seed to assure the formation of a vitreous state that minimizes the possibility of the generation of ice crystals in the seed cells. Due to this obstacle, the objective of this work was to establish a protocol for cryopreservation of A. angustifolia seeds, targeting for the maintenance of the physiological quality for prolonged periods. The research was divided into eight experiments, where forms and periods of dehydration, solutions for cryoprotection and forms of freezing of the seeds were tested. The experiments were arranged in a completely randomized design. Tetrazolium tests were performed to evaluate the physiological quality of the seeds, in addition of measuring the variables seedling emergence, root protrusion and the seed moisture content. The results lead to the following conclusions: there was a progressive reduction of seed moisture content and viability with increasing period of immersion in PVS2 solution. Dehydration in silica gel for 120 hours reduced seed viability, but when glucose (60%) + glycerol (15%) was used for 72 hours, the physiological quality of seeds was maintained. The cryopreservation in liquid nitrogen or ultrafreezer, regardless of pre-treatment used, was lethal to seeds. The acclimatization of the seeds of A. angustifolia for 24 hours in a 3 molar (M) sucrose solution plus 12 hours in solution with 2M glucose + 0.4M sucrose prior to immersion in PVS2 for 24 hours, reduced viability and seed vigour. The freezing of A. angustifolia seeds, using cryoprotectants with glucose (60%) + glycerol (15%), at -5℃ and -18°C for 7 days, were lethal. The acclimatization of the seeds for 15 hours in a 0.3M solution of sucrose plus 8 hours in a 2M glucose + 0, 4M sucrose solution prior to immersion of 12 hours in PVS2 reduced seed viability and vigour. Freezing of acclimated seeds cryoprotected with PVS2, at -5℃ and -18°C for 7 days, was lethal. The results of these experiments not allowed to establish an efficient protocol for cryopreservation of A. angustifolia seeds.